Competency of Registered Nurse with High Potential: Competency of Registered Nurse with High Potential - Kosoom, Kanta; Kosoom , Samai (RATANABUTH JOURNAL, 2025)
The Hospitals both domestically and abroad are adjusting to becoming smart hospitals and caring for patients in digital healthcare. Therefore, it is imperative that the health personnel with the greatest number are registered nurse. Must adapt to be with high potential characteristics. This article therefore aims to study the competency of professional nurses with high potential and found that professional nurses should have the most important competency: develop yourself to be knowledge worker, next is a having competence in nursing practice, turning regular work into research, Information literacy, thinking to solve problems in crisis situations, leadership in health technology, good communication, ability to work as a team, ability to synthesize and differentiate, ability to provide knowledge and give advice, clarity in the law and ethics and Creativity.